Design and evaluation of a dosimetry system to verify the radiotherapy procedure from treatment planning to treatment delivery - upetd@ais.up.ac.za (University of Pretoria, 2013)
Dissertation (MSc (Medical Physics))--University of Pretoria, 2005.